EFFICIENCY OF OPERATION OF AGRARIAN HUMAN CAPITAL - Tsetsiarynets, Tatsiana (Economy and Sociology, 2022)
The article substantiates the identification of agrarian human capital as a specific form of human capital and provides its author’s interpretation. In determining its quantitative value, the advantages of using the income assessment method rather than the cost (investment) approach are proven. The latter circumstance is the basis for the development of methods to assess the effectiveness of its functioning in the agrarian sphere, based on the acme technology. The use of the acmeological approach is conditioned by the necessity of a comprehensive analysis of the process of human capital formation in the agricultural sector of Belarus. This approach considers the individual’s creative and purposeful possibilities and achievements. A system of interrelated indicators, which allows determining the effectiveness of the use of agrarian human capital, is proposed. The main aim of the research is to develop a methodical approach to evaluate the efficiency of the functioning of agrarian human capital. The article was prepared with the use of general scientific research methods and private approaches to solving problems. In particular, the methodology of analysis, synthesis, graphic and tabular methods were used. Practical testing of the proposed assessment methodology shows a decrease in the efficiency of agrarian human capital’s functioning. This is due to the prevailing dynamics of growth of quantitative indicators compared to those of qualitative parameters. The proposed methodological approach to assessing the effectiveness of the functioning of agrarian human capital can be used by the representatives of management bodies, scientists and researchers to develop program documents to form state agrarian and regional policy.